Multi-valued graph contraction principle with applications. (2nd August 2020) - Petruşel, Adrian; Petruşel, Gabriela; Yao, Jen-Chih
ABSTRACT: The aim of this paper is to present a generalization of Nadler's fixed point principle for the case of multi-valued graph contractions. Also, a strict fixed point theorem is obtained. Connections to some variational analysis concepts are discussed and applications to generalized coupled fixed point problems are given.